2020
DOI: 10.3390/ijms21093100
|View full text |Cite
|
Sign up to set email alerts
|

Redox Homeostasis and Metabolism in Cancer: A Complex Mechanism and Potential Targeted Therapeutics

Abstract: Reactive Oxygen Species or “ROS” encompass several molecules derived from oxygen that can oxidize other molecules and subsequently transition rapidly between species. The key roles of ROS in biological processes are cell signaling, biosynthetic processes, and host defense. In cancer cells, increased ROS production and oxidative stress are instigated by carcinogens, oncogenic mutations, and importantly, metabolic reprograming of the rapidly proliferating cancer cells. Increased ROS production activates myriad d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 224 publications
(379 reference statements)
1
58
0
Order By: Relevance
“…It is well described that normal and tumor cells have different redox balances. Many reports have shown that tumor cells counterbalance intrinsic oxidative stress by upregulating antioxidant defense [112,113]. This increase in basal ROS generation renders cancer cells highly dependent on antioxidant systems and more vulnerable to agents that abrogate the antioxidant system and/or increase the ROS level [99,114].…”
Section: Discussionmentioning
confidence: 99%
“…It is well described that normal and tumor cells have different redox balances. Many reports have shown that tumor cells counterbalance intrinsic oxidative stress by upregulating antioxidant defense [112,113]. This increase in basal ROS generation renders cancer cells highly dependent on antioxidant systems and more vulnerable to agents that abrogate the antioxidant system and/or increase the ROS level [99,114].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular ROS level is tightly controlled through a battery of antioxidant defenses, both enzymatic and nonenzymatic (small molecules) antioxidants ( Figure 1 ). Oxidative stress is a condition that occurs when there is an imbalance between ROS generation and antioxidant response, leading to an excess of ROS [ 29 , 32 ]. ROS—mostly the free radicals superoxide anion O 2 −.…”
Section: Ros and Cancermentioning
confidence: 99%
“…The prominent role these couples play in central metabolism is highlighted in Figure 3 . Metabolic therapy aimed at restoring these ratios is often used as an adjunct to more targeted therapies [ 15 ]. The ketogenic diet as a treatment for childhood epilepsy has drawn focus to (R)-beta-hydroxybutyrate (R-BHB) as a metabolic therapy.…”
Section: Introductionmentioning
confidence: 99%